OP0133 ONE-YEAR PROGRESSION OF EROSIVE DISEASE EVALUATED WITH HIGH-RESOLUTION PERIPHERAL QUANTITATIVE COMPUTED TOMOGRAPHY IN PATIENTS WITH ANTI-CITRULLINATED PEPTIDE ANTIBODIES AND ARTHRALGIA. (June 2019) - Keller, Kresten Krarup; Thomsen, Jesper Skovhus; Stengaard-Pedersen, Kristian; Therkildsen, Josephine; Nielsen, Andreas Wiggers; Schiøttz-Christensen, Berit; Svendsen, Lone; Graakjær, Merete; Petersen, Peter Mosborg; Unger, Barbara; Kjær, Gøren Geil; Langdahl, Bente; et al.
Abstract : Background: Bone erosions are common at diagnosis of rheumatoid arthritis (RA). However, bone erosions in preclinical RA (pre-RA) are not well described, and have not been studied prospectively. High resolution peripheral quantitative computed tomography (HR-pQCT) has a spatial resolution of 82 µm and may therefore be ideal to detect bone erosions. Objectives: To evaluate erosive progression with HR-pQCT in anti-citrullinated peptide antibody (ACPA) positive patients with arthralgia compared with healthy subjects. Methods: Patients were recruited by specialists in rheumatology at hospital clinics and in private practice, and healthy controls were recruited from a website for research subjects. Patients with arthralgia, ACPA and no rheumatic disease, and controls without arthralgia, ACPA, or rheumatic disease were included. Medical history, ACPA, clinical examination and ultrasound of symptomatic joints were performed in all patients and controls. A 2.7-cm-long volume of interest in the 2 nd and 3 rd MCP joint of the right hand was HR-pQCT scanned at a spatial resolution of 82 µm at baseline and after one year. Cortical and trabecular bone structure were evaluated in a 12.3-mm-long volume of interest proximal to the MCP head using the provided scanner software. Erosions were defined as cortical breaks in two consecutive slices, in two planes, non-linear in shape, and with loss of underlying trabecular structure. Number, depth, width, and volume of erosions were measured using the Osirix DICOM viewer. Intra observer agreement for erosions was evaluated with Cohens Kappa and coefficient of variance (CV). Values are median(interquartile range). Results: Twenty-two patients (aged 53(36-63) years) and 23 controls (aged 48 (42-57) years) were evaluated. Ten patients were diagnosed with RA after 86(24-200) days. There was a significant increase in the number of patients with erosions during follow-up in the patient group (4 vs. 10, p =0.031), but not in the control group (1 vs. 4, p =0.083). In addition, at follow-up more erosions per individual were demonstrated in patients compared to controls ( p= 0.031). The increase in average and total volume of erosions from baseline to follow-up were larger in patients compared with controls (Fig. 1) ( p =0.031 and p =0.027). At follow-up average and total width, depth and volume of erosions were larger in patients compared with controls ( p between 0.031 and 0.045). Percent change in bone density, cortical, as well as trabecular parameters did not differ between patients and controls. Agreement was 95% equivalent to a kappa of 0.89 for erosions. CV for width, depth, and volume of erosions were 8%, 23%, and 39%. Conclusion: Progression of erosive disease in ACPA positive patients with arthralgia using HR-pQCT is reported for the first time. The results highlight that an even earlier diagnosis of RA is crucial to prevent erosive disease. Disclosure of Interests: Kresten Krarup Keller Speakers bureau: Have received speaking fee from Pfizer, Jesper Skovhus Thomsen: None declared, Kristian Stengaard-Pedersen: None declared, Josephine Therkildsen: None declared, Andreas Wiggers Nielsen: None declared, Berit Schiøttz-Christensen: None declared, Lone Svendsen: None declared, Merete Graakjær: None declared, Peter Mosborg Petersen: None declared, Barbara Unger: None declared, Gøren Geil Kjær: None declared, Bente Langdahl: None declared, Ellen Margrethe Hauge Grant/research support from: Have received grants from Roche and Novartis, outside the submitted work., Speakers bureau: Have received personal fees from MSD, Pfizer, UCB and Sobi